Applications of perturbations on accretive mappings to nonlinear elliptic systems involving (p,q)-Laplacian - Wei, Li; Agarwal, R.P.; Wong, P.J.Y. (Нелінійні коливання, 2009)
Using perturbation results on sums of ranges of nonlinear accretive mappings of Calvert and Gupta, we present some abstract results about the existence of solutions of nonlinear Neumann elliptic systems involving (p, q)-Laplacian. The systems discussed in this paper and the method used extend and complement some of the previous work.